Crystal growth in the low-temperature deposition of polycrystalline silicon thin film - Shin, SD; Kim, DW; Kim, DK; Kim, DY (ELSEVIER SCIENCE BV, 2005)
In this study. the microstructure and property of poly-Si film, deposited using hot wire chemical vapor deposition (HWCVD) were investigated. A consequence of the low a-Si content in the poly-Si film was crystallites with well developed facets. The crystallite morphology was rhombic pyramidal while EBSD analysis revealed the existence of (1 1 1) contact twin planes. The facets of the rhombic pyramidal crystallites were based oil {3 2 0} and {3 2 0}* planes, which have Sigma3 twin relationship with respect to (1 1 1) contact twin plane. (C) 2004 Published by Elsevier B.V.
Keywords: CHEMICAL-VAPOR-DEPOSITION; FLATTENED DIAMOND CRYSTALS; HOT-WIRE CVD; MICROCRYSTALLINE SILICON; SOLAR-CELLS; SI; MECHANISM